APLIKASI SISTEM PAKAR DIAGNOSA PENYAKIT GASTROENTERITIS BERBASIS ANDROID DENGAN METODE CLASSIFICATION AND REGRESSION TREE - I Dewa Made Krisnayana; Putu Arya Mertasana; Made Sudarma (Program Studi Teknik Elektro UNUD, 2020)
Gastroenteritis is a disease that attacks the body's digestive system, especially in thesmall intestine and stomach through viruses and bacteria. In addition to its transmission causedvirus and bacteria, it can also caused by unhygienic food and drink. However, people generallyequate gastroenteritis with diarrheal disease, causing medical mismanagement that can befatal. Therefore, this research trying to build an Android based application that can help peoplein diagnose gastroenteritis. So in this research, the application was build using ClassificationAnd Regression Tree using an Android platform and flutter extension. This research usinghistorical data of 780 patients with 2 classes of disease, namely gastroenteritis and gastritis.The testing results is done to determine the peformance of application such as accuracy,precision , and recall of the application in diagnosing disease. According to confusion matrixtesting results, the application that was build able to diagnose gastroenteritis and gastritisdisease by obtaining an Accuracy of 85.1 %, Precision of 84 %, and Recall (applicationsensitivity in diagnosing) of 98 %.